Selection for health professions education leads to increased inequality of opportunity and decreased student diversity in The Netherlands, but lottery is no solution: A retrospective multi-cohort study. (3rd July 2022) - Mulder, Lianne; Wouters, Anouk; Twisk, Jos W. R.; Koster, Andries S.; Akwiwu, Eddymurphy U.; Ravesloot, Jan H.; Croiset, Gerda; Kusurkar, Rashmi A.
Abstract: Background: Concerns exist about the role of selection in the lack of diversity in health professions education (HPE). In The Netherlands, the gradual transition from weighted lottery to selection allowed for investigating the variables associated with HPE admission, and whether the representativeness of HPE students has changed. Method: We designed a retrospective multi-cohort study using Statistics Netherlands microdata of all 16-year-olds on 1 October 2008, 2012, and 2015 ( age cohorts, N > 600, 000) and investigated whether they were eligible students for HPE programs ( n > 62, 000), had applied ( n > 14, 000), and were HPE students at age 19 ( n > 7500). We used multivariable logistic regression to investigate which background variables were associated with becoming an HPE student. Results: HPE students with ≥1 healthcare professional (HP) parent, ≥1 top-10% income/wealth parent, and women are overrepresented compared to all age cohorts. During hybrid lottery/selection (cohort-2008), applicants with ≥1 top-10% wealth parent and women had higher odds of admission. During 100% selection (cohort-2015) this remained the case. Additionally, applicants with ≥1 HP parent had higher odds, those with a migration background had lower odds. Conclusions: Odds of admission are increasingly influenced by applicants' backgrounds. Targeted recruitment and equitable admissions procedures are required to increase matriculation of underrepresented students.